KEBIJAKAN HUKUM DALAM MELINDUNGI PEREMPUAN DARI PERZINAAN DAN PROBLEMATIKA NIKAH SIRRI - Sianturi, Roiko Frans; Zarzani, T Riza; Fitrianto, Bambang; Anwar, Yohny; Sinaga, Hary Angga (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2021)
Marriage is an effort to channel the sexual instincts of a husband and wife in a lawful manner in the household as well as a means to produce offspring that can ensure the continuity of the existence of a family. However, not everyone can and is able to carry out a marriage as regulated by the State, because of many factors that become a barrier. Based on that argument, the sirri marriage is the alternative that many parties choose to validate a relationship. However, many people oppose this choice, because there are so many losses that will be received by mothers and children, from the status of the child's birth from a sirri marriage, especially if there is a divorce. In Indonesia, where the majority of the adherents are Muslims, this phenomenon is very widespread, however for various reasons sirri marriage remains the choice of many married age couples. The case of siri marriage to validate a relationship is not new. In a census conducted by a non-governmental organization (NGO) for the Empowerment of Women Heads of Family (Pekka), 25 percent of people in Indonesia practiced unregistered and customary marriages in 2012, meaning that these marriages were not registered in the country. Adultery in Indonesia makes us unable to close our eyes and has to find a solution. Many factors cause the high rate of adultery, including uncontrolled lust, fear of choosing a sirri marriage with all its negative consequences, not yet economically established, and unwilling to be bound in a legal marriage However, the point of view of this study is to try to side with the alternative to sirri marriage, which should be an option rather than committing adultery. This argument starts from an illustration because of the unequal number of men and women. Data from the Central Bureau of Statistics are 110 men per 100 women out of Indonesia's 254.9 million population (2015). This figure is of course significant with the large number of women in Indonesia who do not have a partner to marry, while choosing a sirri marriage remains a frightening specter, so adultery is the way to be taken as a channel for their lust. Now the questions are, 1) can the phenomenon of sirrri marriages be stopped? 2) what factors cause the perpetrators of sirri marriages to increase every year ?, and 3) whether sirri marriages are an alternative that should be taken compared to committing adultery, considering the Indonesian nation the majority of Muslims and Muslims strongly oppose all forms of adultery.